Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1158/1940-6207.capr-18-0437
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Encapsulation Enhances the Bioavailability and Tissue Retention of Curcumin and Improves its Efficacy in Preventing B[a]P-induced Lung Carcinogenesis

Abstract: The rate of lung cancer incidence is alarmingly mounting, despite the decline of smoking and tobacco consumption. Recent reports indicate a very high correlation between the growing fast food culture and lung cancer incidence. Benzo[a]pyrene (B[a]P) is a potent carcinogen abundantly present in grilled and deep-fried food and in tobacco smoke. Our previous studies have proved the efficacy of curcumin in curbing B[a]Pinduced lung carcinogenesis. However, the poor pharmacokinetic profile of the compound considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 52 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…In a recent study, curcumin loaded chitosan NPs with a size of about 200 nm were prepared to be used as a chemotherapeutic agent for lung cancer. The results of this research confirmed a significant improvement in the cytotoxicity of the drug-loaded nanocarrier and also introduced this type of nanosystem as an oral supplement against environmental carcinogenesis [142]. In another study, curcumin was loaded into a pH-responsive nanocapsule that is composed of mesoporous silica and chitosan for using against the U87MG glioblastoma cancer cell line.…”
Section: Chitosansupporting
confidence: 62%
“…In a recent study, curcumin loaded chitosan NPs with a size of about 200 nm were prepared to be used as a chemotherapeutic agent for lung cancer. The results of this research confirmed a significant improvement in the cytotoxicity of the drug-loaded nanocarrier and also introduced this type of nanosystem as an oral supplement against environmental carcinogenesis [142]. In another study, curcumin was loaded into a pH-responsive nanocapsule that is composed of mesoporous silica and chitosan for using against the U87MG glioblastoma cancer cell line.…”
Section: Chitosansupporting
confidence: 62%
“…These NPs can be delivered directly to the deeper alveolar tissues optimizing lung therapy with efficient drug delivery [ 125 ]. Additionally, the incorporation of curcumin to chitosan NPs has shown an excellent anti-inflammatory effect [ 126 , 127 ].…”
Section: Nanotechnology-based Drug Delivery Systems In Ardsmentioning
confidence: 99%
“…Cur CS NPs evaluation studies were conducted to improve Cur properties for oral administration, since this compound has low bioavailability and aqueous solubility [119]. Vijayakurup et al [120] led in vivo pharmacokinetic studies with Cur CS NPs, which presented greater cellular uptake and Cur retention comparing to the nonencapsulated form, verifying the sustained release of Cur for 180 h. The NPs also demonstrated pharmacological safety, due to their nontoxic properties and, moreover, were able to reduce tumoral incidence and multiplication in pulmonary adenocarcinoma induced by benzo(a)pyrene.…”
Section: Cs Nanoparticles For Curcumin Deliverymentioning
confidence: 99%
“…Stronger anti-Candida albicans effect than chlorhexidine; mouth ulcer decrease and better healing compared to benzidamine [148] In vivo Cytotoxicity effect against lung cancer (H1299 cells) in animal model induced by benzopyrene Size: 170-200 nm; Sustained release; increase of bioavailability; expressive cell capture; greater reduction of H1299 cells viability [120] compared to free Cur…”
Section: Candida Albicansmentioning
confidence: 99%